THE INFLUENCE OF HYPERTEXT-BASED HISTORY TEACHING METHOD TOWARDS THE INCREASE OF HISTORICAL UNDERSTANDING - Arif, Muhamad (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2010)
This study was aimed at gaining a comprehensive overview of the influence of hypertext-based history teaching method towards the increase of historical concept understanding. The method used in the study was experimental method, i.e. through non – equivalent control group design (pre-test and post-test). Some points were concluded from the data collected within the study. First, the implemented hypertext-based history teaching model had affected learning activities to focus more on mental activities (thinking process). The whole teaching learning activities benefitted the students a wide chance to study, observe, compose, deliver the questions, answer them, consider others’ view, discuss questions by relating them with textual concepts, and make conclusion together. Second, the hypertext-based history teaching model test showed was proved to that the influence the increase of historical concept mastery was increased by n gain of 0.5 at the experimental class, 0.4 at the control class, with significance value of 0.00 and α = 0.05